Sanctions, short-term mindsets, and delinquency: Reverse causality in a sample of high school youth - Gelder, Jean-Louis van (Legal and criminological psychology, 2020)
PURPOSE-We question the commonly assumed view of a fixed causal ordering between self-control, delinquency, and sanctions and test the hypothesis that experiencing sanctions may reduce levels of self-control, thereby increasing the risk of future delinquent behaviour. As a subsidiary goal, we argue for a parsimonious view of self-control that is limited to its key components, risk-taking, and impulsivity.METHODS-We use three waves of data from the Zurich Project on the Social Development from Childhood into Adulthood (z-proso), an ongoing prospective longitudinal study of Swiss urban youth (N = 1,197), and include police contacts and school sanctions as predictors of delinquency. We test our hypothesis using path analysis and control for a series of potential confounders, including prior levels of self-control and earlier delinquency.RESULTS-In line with our hypothesis, the results indicate that sanctioning reduces levels of self-control, net of prior levels of self-control, and earlier delinquency and that self-control mediates the relation between sanctioning and subsequent delinquency.CONCLUSIONS-We conclude that the relation between self-control and crime may be bi- rather than unidirectional with sanctions reducing levels of self-control, which in turn contributes to criminal behaviour. Implications for theory are discussed.